18F-FDG PET/CT in the Diagnosis and Follow-up of Balint Syndrome. (February 2021) - Dondi, Francesco; Albano, Domenico; Paghera, Barbara; Bertagna, Francesco; Giubbini, Raffaele
Abstract : Abstract: Balint syndrome is a rare neurological disorder characterized by simultanagnosia, optic ataxia, and ocular apraxia, and its etiology can be very heterogeneous. Diagnosis is based on neuropsychological evaluation, but brain radiological and nuclear medicine imaging also plays an important role. Because few case reports have been published in literature, in this work, we present 2 patients affected by Balint syndrome in which 18 F-FDG PET/CT helped in the diagnosis and follow-up.